The Peran Guru Dalam Mengaplikasikan Strategi Manajemen Kelas yang Efektif dalam Meningkatkan Partisipasi Siswa - Utomo; Nutfah Tiara Agustin (Nusa Putra University, 2024)
This study aims to explore the teacher's role in applying effective classroom management strategies to increase student participation in class, and to create a conducive learning environment, where students will be actively involved in the learning process. This study uses a qualitative approach by collecting data through classroom observations and interviews with teachers who have experience in implementing classroom management strategies. The research results show that the teacher's role is very important in applying effective classroom management strategies. The teacher acts as a class leader who is able to create a conducive environment, provide clear guidelines, and facilitate positive interactions between students. Then, the teacher is also responsible for managing learning time, providing constructive feedback, and motivating students to actively participate in the learning process. learning. So it can be concluded that this study emphasizes the important role of the teacher in applying effective classroom management strategies to increase student participation. Teachers need to have a deep understanding of these strategies and be able to adapt them according to the needs and characteristics of students. Thus, it is hoped that a conducive learning environment can be created, so that student participation increases and the learning process becomes more effective